Simultaneous disruption of two DNA polymerases, Polη and Polζ, in Avian DT40 cells unmasks the role of Polη in cellular response to various DNA lesions. - Kouji Hirota; Eiichiro Sonoda; Takuo Kawamoto; Akira Motegi; Chikahide Masutani; Fumio Hanaoka; Dávid Szüts; Shigenori Iwai; Julian E Sale; Alan Lehmann; Shunichi Takeda (PLoS Genetics)
Replicative DNA polymerases are frequently stalled by DNA lesions. The resulting replication blockage is released by homologous recombination (HR) and translesion DNA synthesis (TLS). TLS employs specialized TLS polymerases to bypass DNA lesions. We provide striking in vivo evidence of the cooperation between DNA polymerase η, which is mutated in the variant form of the cancer predisposition disorder xeroderma pigmentosum (XP-V), and DNA polymerase ζ by generating POLη(-/-)/POLζ(-/-) cells from the chicken DT40 cell line. POLζ(-/-) cells are hypersensitive to a very wide range of DNA damaging agents, whereas XP-V cells exhibit moderate sensitivity to ultraviolet light (UV) only in the presence of caffeine treatment and exhibit no significant sensitivity to any other damaging agents. It is therefore widely believed that Polη plays a very specific role in cellular tolerance to UV-induced DNA damage. The evidence we present challenges this assumption. The phenotypic analysis of POLη(-/-)/POLζ(-/-) cells shows that, unexpectedly, the loss of Polη significantly rescued all mutant phenotypes of POLζ(-/-) cells and results in the restoration of the DNA damage tolerance by a backup pathway including HR. Taken together, Polη contributes to a much wide range of TLS events than had been predicted by the phenotype of XP-V cells.